Pemantauan pH Produk Skincare berbasis IoT: Solusi untuk Keamanan Konsumen - Pieters, Luntungan Stephen (Jurnal Pendidikan Informatika (EDUMATIC), 2025)
Skincare products play an important role in skin health, but there is often a discrepancy between the product content and the information on the label, which can harm consumers. This research aims to develop an IoT-based pH monitoring system with a digital pH sensor and UV-Vis spectroscopy to detect changes in pH in real-time, provide more accurate data, and improve efficiency in monitoring the quality of skincare products. The method used is a development approach with a prototype model, which integrates an IoT system with a digital pH sensor and UV-Vis spectroscopy. The system is designed to measure the pH of skincare products based on the principle that each compound absorbs light at a specific wavelength. The tested product samples consist of five types of skincare facial cleansers, toners, serums, moisturizers, and sunscreens that are illuminated with UV-Vis light to measure absorbance values. The pH data obtained was statistically analyzed to calculate the pH deviation compared to the value on the packaging label. Results showed the system was able to detect real-time pH changes with an average deviation below 0.2 for most products, although serums showed larger deviations. The system improves transparency and quality control, helping manufacturers ensure products meet safety standards and giving consumers confidence in choosing safe products.